Tanjidor Your History Now: The Cultural Condition of Tanjidor in the Eyes of Generation Z - Fauziah Fauziah; Murtarsiah Murtarsiah; Vrio Andris; Rosalita Rosalita; Widahayati Widahayati (CV. Publikasi Indonesia, 2023)
Tanjidor is a type of entertainment art of the Betawi tribal orchestra that uses western musical instruments, especially wind instruments. Tanjidor was originally developed from a colonial environment. this art entered Indonesia in the 18th century through trade routes which at that time were played to accompany or parade brides. This art is played to enliven various events such as weddings, circumcisions and birthday events of the Jakarta city government.The method used in this study is qualitative with a descriptive method. The subjects of this study are the owners of tanjidor cultural studios, tanjidor players and generation Z who in this study are students of MTs N 35 Jakarta grade 7, 8 and grade 9.The results of this study show that the existence of tanjidor music art in Jakarta is influenced by various factors, namely changing tastes in society while the inhibiting factors are the entry of western art and the change of agrarian society into an industrial society. To overcome the challenges of the existence of tanjidor art in society, namely by modernizing tanjidor culture.one thing is certain, tanjidor music art is still popular among generation Z.